Multimode Coordination Control of a Hybrid Active Suspension - Fa-Rong Kou; Dong-Dong Wei; Lei Tian (Shock and Vibration)
In order to effectively realize the damping control and regenerative energy recovery of vehicle suspension, a new kind of hybrid active suspension structure with the ball screw actuator and magnetorheological (MR) damper is put forward. Firstly, for the analysis of the suspension performance, a quarter dynamic model of vehicle hybrid suspension is established, and at the same time, the mathematical models of MR damper and ball screw actuator are founded. Secondly, the active mode with damping switching control of the hybrid suspension and the semiactive mode with feedback adjustment of the electromagnetic damping force of the hybrid suspension are analyzed. Then, the multimode coordinated control system of the hybrid suspension is designed. Under the cyclic driving condition, the damping performance and energy consumption characteristics of the hybrid suspension are simulated by MATLAB/Simulink software. Finally, the bench tests of the hybrid suspension system are done. The simulation and experimental results show that compared with passive suspension, the root mean square of the sprung mass acceleration of the hybrid suspension with the active mode and semiactive mode is, respectively, reduced by 39% and 16% under the random road. The damping effect of the hybrid suspension system is obvious.